Porcentaje óptimo de propóleos como agente bioconservante en la longaniza artesanal - Vélez Mendoza, María Lourdes (2019)
This research was carried out in order to evaluate the optimal percentage of propolisas a bio-conservative agent in artisanal sausage by applying the factors (A): percentage of propolis with the following levels: a1 = 1%, a2 = 1.5 % y a3 = 2% and storage temperature (B) with the following levels: b1 = (25 - 31 ° C), b2 = (4 - 7 ° C) making three replications, giving a total of 18 experimental units. To verify the normal distribution of the data obtained, the assumptions of the ANOVA (Normality and homogeneity) were carried out using the Shapiro Wilk statistical test. The test showed that the data was not distributed normally, going on to analyze the data through non-parametric tests with the Kruskal – Wallis statistical test. Using the nonparametric Kruskal – Wallis test of independent samples, factor A was contrasted with the response variable (CFU / g mesophilic aerobes) demonstrating that the distribution between these two variables is the same. On the other hand, the factor B contrasted with the response variable showed a significance, that is to say that the temperatures did influence the microbiological growth of the mesophilic aerobes, indicating that there is a better conservation temperature (cooling) because there were no alterations, physicochemical and microbiological, during experimentation. Another of the contrasts that were proposed were the treatments with the response variable, where the Kruskal – Wallis statistical test showed that the distribution of UFC_Log is the same among the treatment categories, which indicates that there is a better treatment.